Current situation and progress toward the 2030 health-related Sustainable Development Goals in China: A systematic analysis - Shu Chen; Lei Guo; Zhan Wang; Wenhui Mao; Yanfeng Ge; Xiaohua Ying; Jing Fang; Qian Long; Qin Liu; Hao Xiang; Chenkai Wu; Chaowei Fu; et al. (PLoS Medicine, 2019)
Background The Sustainable Development Goals (SDGs), adopted by all United Nations (UN) member states in 2015, established a set of bold and ambitious health-related targets to achieve by 2030. Understanding China’s progress toward these targets is critical to improving population health for its 1.4 billion people. Methods and findings We used estimates from the Global Burden of Disease (GBD) Study 2016, national surveys and surveillance data from China, and qualitative data. Twenty-eight of the 37 indicators included in the GBD Study 2016 were analyzed. We developed an attainment index of health-related SDGs, a scale of 0–100 based on the values of indicators. The projection model is adjusted based on the one developed by the GBD Study 2016 SDG collaborators. We found that China has achieved several health-related SDG targets, including decreasing neonatal and under-5 mortality rates and the maternal mortality ratios and reducing wasting and stunting for children. However, China may only achieve 12 out of the 28 health-related SDG targets by 2030. The number of target indicators achieved varies among provinces and municipalities. In 2016, among the seven measured health domains, China performed best in child nutrition and maternal and child health and reproductive health, with the attainment index scores of 93.0 and 91.8, respectively, followed by noncommunicable diseases (NCDs) (69.4), road injuries (63.6), infectious diseases (63.0), environmental health (62.9), and universal health coverage (UHC) (54.4). There are daunting challenges to achieve the targets for child overweight, infectious diseases, NCD risk factors, and environmental exposure factors. China will also have a formidable challenge in achieving UHC, particularly in ensuring access to essential healthcare for all and providing adequate financial protection. The attainment index of child nutrition is projected to drop to 80.5 by 2025 because of worsening child overweight. The index of NCD risk factors is projected to drop to 38.8 by 2025. Regional disparities are substantial, with eastern provinces generally performing better than central and western provinces. Sex disparities are clear, with men at higher risk of excess mortality than women. The primary limitations of this study are the limited data availability and quality for several indicators and the adoption of "business-as-usual" projection methods. Conclusion The study found that China has made good progress in improving population health, but challenges lie ahead. China has substantially improved the health of children and women and will continue to make good progress, although geographic disparities remain a great challenge. Meanwhile, China faced challenges in NCDs, mental health, and some infectious diseases. Poor control of health risk factors and worsening environmental threats have posed difficulties in further health improvement. Meanwhile, an inefficient health system is a barrier to tackling these challenges among such a rapidly aging population. The eastern provinces are predicted to perform better than the central and western provinces, and women are predicted to be more likely than men to achieve these targets by 2030. In order to make good progress, China must take a series of concerted actions, including more investments in public goods and services for health and redressing the intracountry inequities. Shenglan Tang and colleagues report China's current situation and projected achievement of the health related sustainable development goals by 2030. Author summary Why was the study done? China has made impressive progress in the Millennium Development Goals (MDGs) era, which ended in 2015. Despite China’s success in achieving the MDGs, it faces formidable challenges in achieving many targets in the health-related Sustainable Development Goals (SDGs), which have a 2030 target date. Understanding China’s current situation and progress toward achieving these goals is critical to the development of practical solutions for improving population health for its 1.4 billion people in the SDG era. What did the researchers do and find? We conducted an analysis of progress toward the health-related SDGs using data from the Global Burden of Disease (GBD) Study 2016, national surveys, surveillance data from China, and qualitative study results. We developed an index of the attainment of the health-related SDGs, using a scale of 0–100 based on the absolute values of indicators. We adjusted the projection model developed by the GBD 2016 SDG collaborators to produce sex-specific estimates, stratified by province, and explore sex and regional disparities. Around 120 key informants were purposively approached for thematic interviews. This research found that China has achieved several health-related SDG targets, especially on child nutrition and maternal and child health and reproductive health. Nevertheless, China may only achieve 12 out of the 28 selected health-related SDG targets by 2030. There are daunting challenges ahead for China in achieving the targets for child overweight, infectious diseases, noncommunicable disease risk factors, environmental exposure factors, and universal health coverage. Regional disparities were substantial, with eastern coastal provinces generally performing better than central and western provinces in most of the indicators. Sex disparities were clear, with men at higher risk of excess mortality than women. What do these findings mean? To achieve the targets of the health-related SDGs, China must take a series of concerted actions, including increased investment in public goods and services for health, addressing the regional inequities, and tackling the emerging new health challenges to ensure that no one is left behind. In those areas where China has already achieved the SDG targets, the government should synthesize the experiences and good practices that can be applied to the regions/provinces that need to catch up to the level of health development witnessed in developed regions/provinces. The Chinese government needs to examine the root causes of the challenges in achieving the health-related SDGs and develop an action plan to address these causes. The plan should prioritize key policy interventions for target populations and mobilize adequate resources to tackle these health challenges. It is important to address common problems by tackling cross-cutting issues in advancing the health-related SDGs, such as strengthening the enforcement of laws and regulations, establishing effective organizational structures, and human resources development.